Guardians of the galaxy : One in a million you - Caramagna, Joe (Guardians of the Galaxy, 2018)
"After the Guardians narrowly escape Thanos and Korath, Rocket accepts an offer to work for the Collector, while the other Guardians search for Pandorian crystals needed to power the map to the Cosmic Seed"--Publisher.